Skin Erosion and Exteriorisation of a Cardiac Implantable Electronic Device: Modified Surgical Approach (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Skin erosion and exteriorization of the commonest cardiac implantable electronic device (CIED) is usually caused by localized infection as a result of “pocket” infection. But, there are other recognized factors including an advanced age with thin, fragile skin with precarious subcutaneous fat. So, exteriorisation of a generator, and/or a lead, is not always associated with bacterial contamination followed by antibiotic therapy and contra-lateral re-implantation strategy. Hence, it does not always make the removal of the material an obligation. Our notable findings in a rare case of such exteriorization stimulate us to look for and implement a modified surgical technique. This 93-year-old extremely aged wonderfully co-operative, multi-morbid woman had multiple episodes of skin erosion and fixation, re-fixation surgery till the best result achieved. We present a new technique for cardiac pacing allowing for full patient recovery via an alternative surgical way of CIED relocation.J Bangladesh Coll Phys Surg 2020; 38(3): 155-157